Transporte coletivo público na cidade de São Luís-MA: comparações pré e pós-implantação do SIT - Sistema Integrado de Transportes - Sousa, Bruno Leonardo Maciel de (2012)
This work aimed to verify the changes that occurred in three items of public transport system in São Luís-MA. We studied the provision of services, travel time lines and opinions of the interviewees. The study was done by comparing data from surveys in 2000 and 2011. The survey results in 2000 were obtained from the VERTRAN, the company that prepared the studies at that time. In the surveys of 2011, in order to study the provision of transport services system, secondary data were collected by the Municipal Office of transit and transport. In the item travel time lines the results were obtained through surveys embedded in six lines, three trips in each morning peak, between peak and afternoon peak. Obtaining data on the opinions of the interviewees was conducted through questionnaires directly to the users at the bus stations and points of embarkation and disembarkation. In relation to the provision of transport service, the analyzes found a growth index (quantity lines; quantity trips, fleet, etc..) below the demand, this indicates that the public transport system is below the need. In the section travel time lines, the results indicate that the analyzed lines have increased the total travel time, and especially the delay time for stops at traffic jams. The result of comparing the opinions of the interviewees showed that their profile has undergone some changes (occupation, income level, etc..) And their views on existing problems in public transport system continue to indicate the existence of such difficulties pointed out in 2000, but it has increased the indication of some items and worsening in business valuation and management bureau. It is concluded that the three items items studied had significant differences: different growth between supply and demand, causing imbalance in service; it has increased the travel time lines, causing difficulties for passengers, and worsening in the evaluation of services by users.